2005
DOI: 10.1089/ten.2005.11.1574
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Endothelialization of Collagen-Blended Biodegradable Polymer Nanofibers: Potential Vascular Graft for Blood Vessel Tissue Engineering

Abstract: Electrospun collagen-blended poly(L-lactic acid)-co-poly(epsilon-caprolactone) [P(LLA-CL), 70:30] nanofiber may have great potential application in tissue engineering because it mimicks the extracellular matrix (ECM) both morphologically and chemically. Blended nanofibers with various weight ratios of polymer to collagen were fabricated by electrospinning. The appearance of the blended nanofibers was investigated by scanning electron microscopy and transmission electron microscopy. The nanofibers exhibited a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
187
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(192 citation statements)
references
References 33 publications
1
187
1
3
Order By: Relevance
“…40,43 Molecular structure X-ray diffraction is commonly used to determine the crystal structure of polymer fibers. 15,20,42,52 Often after chemical modification or the attachment of functional groups, the molecular structure is determined using FTIR 42,43,85,86 or nuclear magnetic resonance analysis. 52 …”
Section: Drug and Protein Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,43 Molecular structure X-ray diffraction is commonly used to determine the crystal structure of polymer fibers. 15,20,42,52 Often after chemical modification or the attachment of functional groups, the molecular structure is determined using FTIR 42,43,85,86 or nuclear magnetic resonance analysis. 52 …”
Section: Drug and Protein Distributionmentioning
confidence: 99%
“…25 Other approaches have included collagen directly into the electrospinning process, creating collagen-blended P(LLA-CL) fibers, which were shown to promote endothelial cell spreading, attachment, and viability. 86 Similarly, core/ shell nanofibers have been created with gelatin in the shell to promote cell adhesion and proliferation, whereas poly (glycerol sebacate) was used as the core to mimic the mechanical properties of heart muscle. These fibers were shown to support the cardiogenic differentiation of MSCs, indicating the potential of the nanofibers in the repair of myocardium.…”
Section: Cardiovascular Tissue Engineeringmentioning
confidence: 99%
“…Electrospinning of a blended collagen mixture is not only simpler, but also avoids the slow mass transfer process and uses lesser amounts of chemical reagents. Moreover, the existence of collagen on the surface and inside the structure provides sustained cell recognition signals with polymer degradation, which is crucial for cell function and development [33].…”
Section: Electrospinning Collagen and Synthetic Polymer Blendsmentioning
confidence: 99%
“…In a study done by He et al [33], it was demonstrated that collagen type I blended poly (L-lactic acid)-co-poly(ε-caprolactone) [(PLLA-CL), 70:30] biohybrid scaffolds could enhance the viability, spreading and attachment of human coronary artery endothelial cells (HCAECs) and preserve their phenotype. A similar approach was used by Kwon and Matsuda [34] to combine PLLA-CL with collagen type I. Scaffolds blended with collagen were found to increase the attachment, spreading and proliferation of human umbilical vein endothelial cells (HUVECs).…”
Section: Electrospinning Collagen and Synthetic Polymer Blendsmentioning
confidence: 99%
“…At first, along with the identification and separation of ECM components, more and more ECM proteins have been used to modify CVIs, such as fibronectin (FN), laminin (LN), and collagens (Col). 1,10,11 Furthermore, during the construction of an artificial ECM on CVIs, several techniques, including electrostatic spinning and microcontact printing, have been taken to mimic the physical characteristics of the natural ECM. 12,13 Even so, when these artificially constructed ECMs were compared with ECMs deposited in situ by cultured cells, the latter ones could mimic the natural ECM to a much greater extent, and presented far superior biological properties.…”
Section: Introductionmentioning
confidence: 99%